High AOA short landing robust control for an aircraft. Issue 1 (18th October 2018) - Tingting, Yang; Aijun, Li; Taimoor, Muhammad; Amin, Rooh ul
Abstract : Purpose: The purpose of this paper is to propose a high angle of attack short landing model for switched polytopic systems as well as to derive an equation for fluidic thrust vector deflection angle based on pressure to reduce the velocity during the landing phase of flight. Design/methodology/approach: In this paper, robust control algorithm is proposed for a non-linear high angle of attack aircraft under the effects of non-linearities, tottering hysteresis, irregular and wing rock atmosphere. High angle of attack short landing flight under asynchronous switching is attained by using the robust controller method. Lyapunov function and the average dwell time scheme is used for obtaining the switched polytopic scheme. The asynchronous switching and loss of data are controlled asymptotically. The velocity of aircraft has been lucratively reduced during the landing phase of flight by using the robust controller technique. Findings: The proposed algorithm based on robust controller including the effects of non-linearities guarantee the successful reduction of velocity for high angle of attack switched polytopic systems. Practical implications: As the landing phase of an aircraft is one of the complicated stage, this algorithm plays a vital role in stable and short landing under the condition of high angle of attack (AOA). Originality/value: In this paper, not only the velocity of flight has been reduced, but also the high angle of attack has been attained during the landing phase, because of which the duration of landing has been reduced as well, while in most of the previous research, it is based on low angle of attack and long landing duration.